Strategi Pengembangan Usaha Produk Olahan Pangan Lokal Berbasis Telur Asin Kelompok Usaha Ekonomi Masyarakat (Kuem) Desa Sujung - Suherman Suherman; Gugun Gunawan; Siti Widiati (JURNAL AGRIBISNIS TERPADU, 2021)
Business Development Strategy for Local Processed Food Products Based on Salt Eggs Community Economic Business Group (KUEM) Sujung Village. The Community Economic Business Group (KUEM) of Sujung Village is a salted egg-based food processing partnership, the KUEM was established as an effort to accelerate the increase in the economic activities of rural communities. The research was conducted at KUEM in Sujung Village, Tirtayasa District, Serang Regency. The purpose of the research is to provide alternative strategies for overcoming problems and strategies for developing KUEM in Sujung Village. The method in this research is the survey method, with a quantitative descriptive approach, and SWOT analysis for problem-solving and alternative strategies in business development carried out by KUEM in Sujung Village. The Sujung Village KUEM business development strategy can do the following: S-O strategies include: a) Improving product quality to attract customers, especially for new products such as Salted Egg Powder. b) The existence of community empowerment for both breeders and food processing. ST strategies that can be applied: a) Maintaining product quality, b) Innovating in product diversification, c) Increasing sales competitiveness, d) Highlighting product advantages, e) Having capital reserves if at any time the price of raw materials rises. Alternatives to overcome business weaknesses, by implementing the WO strategy: a) Conduct training for workers to improve quality and production output, b) Increase business capital, c) Create new flavors, d) Expand marketing through social media to make the product better known to the public. outside Banten. WT Strategy: a) Maintaining good relations with customers and distributors of processed products and suppliers of raw materials, b) Observing business competitors' products, c) Expanding marketing channels, d) In the COVID-19 condition, implementing an online marketing system.